A dual-polarized metamaterial-based cloak. (December 2017) - Islam, Sikder Sunbeam; Iqbal Faruque, Mohammad Rashed; Islam, Mohammad Tariqul
Graphical abstract: Highlights: A new artificial metamaterial has been designed. The metamaterial has wideband negative permittivity region. A new rectangular invisibility cloak has been built using the metamaterial. The cloak operates with wideband for dual-polarization. Operating band of the cloak covers C-and X-band. Abstract: A new metamaterial-based dual-polarized rectangular single layer electromagnetic invisibility cloak is being introduced in this study. Initially, a bare-H-shaped metamaterial unit cell was designed on FR-4 dielectric material. Finite integration technique-based electromagnetic simulator was adopted to design the metamaterial and explore the material's effective medium properties. Measured result for the metamaterial was provided as well. Then the proposed metamaterial was employed in the construction of a new dual-polarized rectangular cloak. The newly developed cloak shields a metal object from view electromagnetically by controlling the electromagnetic fields. The cloak was found performing the cloaking operation from the frequency of 5.04 GHz–9.47 GHz that covers certain region of C- and X-band of microwave spectrum.